The role of macrophages in early phases of type 2 diabetes mellitus - Gunaseelan, Divya (2018)
Inflammatory response is a hallmark process of type 2 diabetes mellitus (T2DM) development and progression. In overt hyperglycaemia, low-grade inflammation of the pancreatic islets is known to cause β-cell dysfunction paving way for the pathogenesis of T2DM. Macrophages are vital elements of the immune system that play a major role in both innate and adaptive immune responses. Increased macrophage infiltration in islets of Langerhans has been documented in humans and rodents with T2DM, thus exposing the islets to a pro-inflammatory milieu and thereby contributing to the disease. Though the detrimental role of islet macrophages in overt T2DM has been widely studied, the role of macrophages in islet cell remodelling during the (very) early stage of pre-diabetes, i.e. the compensatory phase, is hardly known. Elucidating the role of macrophages, and more so islet resident macrophages, along with their contribution to islet remodelling in early stages of T2DM can offer a window of opportunity to delay the progression of the disease. We established an animal model of pre-diabetes by exposing mice to a very short term high-fat diet (HFD) and utilized different established macrophage markers, to understand the dynamics of islet macrophages during this phase of pre-diabetes. We found a significant increase in islet macrophage cells within HFD fed mice at 21-days when compared to mice treated with the iso-calorie low-fat diet (LFD). To further determine whether macrophages play a direct role in islet dysfunction during the initial compensatory phase, we used diphtheria toxin receptor (DTR) mice to deplete macrophages during HFD feeding. Our results suggest that presence of macrophages may be important to promote compensatory islet hyperplasia (growth of islet size) at a much earlier stage of mouse T2DM pathogenesis.